2016
DOI: 10.5664/jcsm.5880
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Nocturnal Cardiac Arrhythmias and Sleep-Disordered Breathing: The DREAM Study

Abstract: SDB is independently associated with nocturnal cardiac arrhythmias. Increasing severity of SDB was associated with an increasing risk for any cardiac arrhythmia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 40 publications
1
39
2
2
Order By: Relevance
“…In other medical conditions, such as sleep‐disordered breathing, hypoxia is a strong predictor of arrhythmia risk, including complex ventricular ectopy, nonsustained ventricular tachycardia, and other cardiac arrhythmias . The relative risk of paroxysmal atrial fibrillation and nonsustained ventricular tachycardia (NSVT) during sleep is markedly increased shortly after a respiratory disturbance …”
mentioning
confidence: 99%
“…In other medical conditions, such as sleep‐disordered breathing, hypoxia is a strong predictor of arrhythmia risk, including complex ventricular ectopy, nonsustained ventricular tachycardia, and other cardiac arrhythmias . The relative risk of paroxysmal atrial fibrillation and nonsustained ventricular tachycardia (NSVT) during sleep is markedly increased shortly after a respiratory disturbance …”
mentioning
confidence: 99%
“…As of now, data indicate that OSA patients with increasing severity of AHI are at graded risk of PVCs, the most frequent type of arrhythmia reported in sleep study [11]. A recent study among US war veterans showed similar increase in overall arrhythmias, especially significant for PVCs and intraventricular conduction delay in patients with sleep apnea [6]. This strong association between OSA and arrhythmia has been ascribed to the structural and functional changes caused by sleep apnea on the heart.These effects have been proposed to be mediated by increased oxidative stress, increased transmural pressures on the heart muscles and excessive sympathetic activities [14].…”
Section: Discussionmentioning
confidence: 59%
“…In the study, he explored the correlation between right bundle branch block (RBBB), ventricular paced rhythm and resting heart rate with OSA. Only recently, with the DREAM study, a graded correlation between OSA severity and ECG abnormalities was highlighted in western population [6]. No data are available on the Indian population in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…It is caused by repeated partial or complete closure of the upper respiratory tract, leading to hypoxaemia, hypercapnia, deterioration of sleep quality and sympathetic hyperactivity [1,2]. OSA is associated with a higher incidence of cardiovascular diseases, including hypertension [3], ischaemic heart disease [4], heart failure [5], stroke [6] and cardiac arrhythmias [7]. It has been proved that sleep apnea causes dysfunction of the autonomic nervous system, but the exact mechanism has not been fully understood [8].…”
Section: Introductionmentioning
confidence: 99%